Estimating the Minimal Number of Repeated Examinations for Random Responsiveness With the Coma Recovery Scale—Revised as an Example - Yang, Hao; Ye, Chengyin; Liu, Xiaochen; Sun, Lingxiu; Wang, Anqi; Wang, Jing; Hu, Nantu; Hu, Xiaohua; Gosseries, Olivia; Laureys, Steven; Di, Haibo; Fang, Jiqian (Frontiers in Integrative Neuroscience, 2021)
Objective: The aim of this study was to develop a general method for estimation of the minimal number of repeated examinations needed to detect patients with random responsiveness given a limited rate of missed diagnosis. Methods: Basic Probability theory was applied to develop the method. As an application, 100 patients in disorders of consciousness (DOC) were assessed by the Coma Recovery Scale–Revised (CRS-R). DOC patients were supposed to be examined for 13 times over 20 days, while anyone who was diagnosed as minimally conscious state (MCS) in a round would no longer be examined in the subsequent rounds. Results: A series of formulas was developed to estimate the probability of a positive response to a single examination given by a patient, and the minimal number of successive examinations needed based on the numbers of patients detected in the first i (i =1, 2, ...) rounds of repeated examinations. As apply to the DOC patients assessed by CRS-R, with a rate of missed diagnosis less than 0.0001, the estimate of the minimal number of examinations was 6 in traumatic brain injury patients while 5 in non-traumatic brain injury patients. Interpretation: The method developed in this paper holds in theory, and works well in application. It should be applicable to any other kind of examinations for random responsiveness, not limited to CRS-R for detecting MCS; this should be validated by further researches.